Predicting Obesity in Young Adulthood from Childhood and Parental Obesity - Whitaker, Robert C; Wright, Jeffrey A; Pepe, Margaret S; Seidel, Kristy D; Dietz, William H (The New England journal of medicine, 1997)
The prevalence of obesity has increased in both children and adults. 1 , 2 The medical illnesses associated with obesity 3 usually occur in adulthood, but adults rarely achieve sustained weight loss. 4 Therefore, prevention of obesity in childhood and effective treatment of overweight children are essential. Although several studies have tracked fatness from childhood to adulthood, 5 – 11 only one study contained data on subjects' height and weight throughout childhood. 11 Whether parental obesity alters the probability that a child will become an obese adult is not known. The purpose of this study was to determine the probability of obesity in young adulthood in relation . . .